spaMGCN: a graph convolutional network with autoencoder for spatial domain identification using multi-scale adaptation - Zhang, Tianjiao; Zhang, Hongfei; Zhao, Zhongqian; Shao, Saihong; Jiang, Yucai; Zhang, Xiang; Wang, Guohua (Genome Biology, 2025)
Spatial domain identification is crucial in spatial transcriptomics analysis. Existing methods excel with continuous and clustered distributions but struggle with discrete ones. We present spaMGCN, an innovative approach specifically designed for identifying spatial domains, especially in discrete tissue distributions. By integrating spatial transcriptomics and spatial epigenomic data through an autoencoder and a multi-scale adaptive graph convolutional network, spaMGCN outperforms baseline methods. Our evaluations demonstrate its effectiveness in recognizing discrete T cell zones in mouse spleens and follicular cells in human lymph nodes, as well as effectively distinguishing capsule structures from surrounding tissues.